Linfoma primário do sistema nervoso central: relato de um caso tratado com sucesso empregando-se quimioterapia em doses elevadas e radioterapia subsequente - Murad, André Márcio (2023)
The authors describe a case of primary central nervous System lymphoma successfully treated with vincristin and intermediate doses of dexametason, Ara-C and methotrexate, which produced a complete remission with minimal toxicity. A llterature review Is presented.